Influencia del marketing digital en el posicionamiento de la organización social Marki en voluntarios en el periodo 2021-2 - Arredondo Jordan, Jefferson Jesús (2022)
The present research aims to identify the degree of Influence of digital marketing in the positioning of the social organization Marki in volunteers in the period 2021-2. The type of research is applied, with a correlative-causal scope and with a quantitative approach. For this research, a virtual survey was applied to 175 Marki volunteers, who meet the profile of being university students or graduates between 20 to 40 years of age who spend much of their time on social networks. The first chapter aims to describe the problem of what is the Influence of digital marketing on the positioning of the social organization Marki in volunteers in the period 2021-2 and to outline the objectives. In the second chapter, the background of the research is presented and references are cited to the theoretical bases that will be useful for the research, as well as basic terminology useful for a better understanding of the report. In the third chapter, the hypotheses conceived according to the research problem foreseen above are presented. Likewise, the variables and ethical aspects of the work are detailed. In the fourth chapter, the methodological design is shown, the delimitation of the research topic, the sample design from which the sample is calculated, the positive relationship of the variables is validated by Spearman's coefficient and the results of the surveys are obtained with their respective graphs. Finally, in chapter five, the conclusions of the study are presented, which sustain that digital marketing has a significant influence on Marki's positioning in the minds of volunteers. Likewise, it ends up giving recommendations so that the organization can optimize its digital tools by attracting and retaining volunteers.